Penerapan Akuntansi Agrikultur SAK EMKM pada Penyusunan Laporan Keuangan Usaha Peternakan Ayam Boiler ( Studi Kasus Peternakan Ayam Boiler Pak Haji Ana Salawu Kabupaten Tasikmalaya) - Dinanda Periska; Hilmi Nabil Muzzaky; Putri Utami; Triani Nurafni (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
The broiler chicken farming sector is a pillar of food security dominated by Micro, Small, and Medium Enterprises (MSMEs); however, its management often falls short of standard financial record-keeping requirements. This study aims to analyze current financial management practices and prepare financial statements based on the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) for Pak Haji Ana's Broiler Chicken Farm in Salawu, Tasikmalaya. A qualitative approach with a case study method was employed, utilizing in-depth interviews, non-participant observation, and documentation. The results indicate that financial recording at this farm is still very simple, with personal and business funds mixed, heavily relying on the Breeder Performance Details (RHPP) document from the partner company. The reconstruction of financial statements demonstrates that the implementation of SAK EMKM can be realized in three components. The Statement of Financial Position records total assets of IDR 405,000,000. The Income Statement shows a net profit of IDR 12,600,000 per harvest cycle (35 days) from a total revenue of IDR 28,500,000. The Notes to the Financial Statements (CALK) detail the reconciliation of biological assets and depletion. This study concludes that despite human resource constraints, the implementation of SAK EMKM is crucial for the transparency and sustainability of partnership-system livestock businesses.